Homeopathy and Haematidrosis—A Case of Calcarea phosphorica - Madsen, Ruy (Homœopathic Links, 2023)
Haematidrosis is a rare disorder characterised by extravasation of blood from intact skin. Most reported cases are in the paediatric age group. We present here a case of haematidrosis in a 9-year-old boy treated with individualised homeopathic remedy selected according to the approaches of the contemporary authors of classical homeopathy. The result was a physical and mental improvement in a 3-year follow-up.
Keywords: haematidrosis; homeopathy; Calcarea phosphorica